Conceptualization of the concept of "business" in the process of teaching a foreign language in a non-linguistic university - Anna L. Morozova; Tat’yana A. Kostyukova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The problem of conceptualization of the lexeme "business" in the process of teaching a foreign language is considered on the example of MGIMO Odintsovo branch (Moscow region). Authors present a study of the conceptualization of the content of education in the process of learning foreign language by students of nonlinguistic training directions in the conditions of implementation of the current Federal state educational standard of higher education 3++ (bachelor's and master's levels) implemented in the educational process of educational institutions of the Ministry of foreign Affairs of the Russian Federation. The methods of working with the concept are described and the algorithm of work is developed, which was successfully tested on the basis of the Institute. The materials of the proposed study, which were made by the national corpus of the English language, authentic textbooks and educational sites, are analyzed. These materials allow students to comprehensively and comprehensively study the concept of "business", and teachers to update the content of education. The communicative orientation of the process of learning a non native language contributes to a comprehensive analysis of this concept from the point of view of the native culture and the culture of the studied language. Proposed basic principles of designing of educational process of the subject: 1) study of the first semester of practice-oriented interpretation in order to fit the specifics of the concept; 2) dialogical process of practicebased communication in a second language in the study of the concept; 3) implementation of scientific-research work of students based on the application of the original literature. The developed algorithm involves the use of various forms of active work of students on the development of the concept: individual, pair and group. The algorithm includes three stages of work: construction of associograms, fixing the concept space and comparison. It is established that the proposed form of work with the concept is aimed not only at the development of educational motivation of students, but also to improve the level of foreign language proficiency of students and foreign language communicative competence.